New quadruple model of active tutoring in an APP experiencie in Advertising and Public Relations Grade from the University of Girona - Sílvia Espinosa-Mirabet; Celia Andreu-Sánchez; Alfons Jiménez Cortacans (Universitat Politècnica de València, 2014)
This paper defines four modes of tutorials created ad hoc in order to develop a specific experience of Learning Project (APP), in the Bachelor of Advertising and Public Relations from the University of Girona. The project has been based on the  development  of  a  comprehensive communication campaign from an actual concrete  custom  client,  in  this  case, the Dean of the Faculty of Tourism. The students have taken on the role of media agencies, teachers have taken the role of campaign managers, and they have corrected their work in the different areas of  their  campaigns:  campaign  advice, online  communication,  audiovisual creation, adverting. Finally, the client role was made by the Dean by acting as a real customer giving students a real and concrete order. The development of the project was made from a systematic and ongoing mentoring that has allowed a combinatorial tutorial, flexible enough to meet the challenge posed to students. Communication   campaigns   were submitted  to  a  heterogeneous,  with the presence of teachers, students and clients. The 4 types of tutorials presented in this new model of university teaching are:  specific  tutorials  weekly,  cross tutorial weekly, tutoring and mentoring rehearsal and evaluation tutorial. The result  is  a  rigorous  experience  that simulates  professional  work  globally serving specific interests and knowledge. We conclude the optimal implementation of  this  quadruple  model  of  active tutoring in an APP experience. The mock pilot was conducted in 2011/2012 and the final execution took place this year 2012/2013.